Determinasi Kinerja Guru SMP Negeri 3 Lasem - Khusnul Khotimah; Susanti Dwi Ilhami (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Educators are a benchmark that builds a generation that is ready to participate in nation building. Educational institutions are the place where teaching and learning activities occur, the success of schools in creating superior students and achievements can be seen through the results of teacher performance. The purpose of this study is to prove the impact of competence, work discipline and physical environment on the performance of SMP N 3 Lasem teachers. This study involved 34 teachers from SMP Negeri 3 Lasem. The sampling method was a saturated sample, and the data analysis was carried out by multiple linear regression analysis using the SPSS 24 tool. This study provides results where the variables of competence and work discipline have a not significant impact on the performance of SMP N 3 Lasem teachers, while the physical environment variables have a significant impact on the performance of SMP N 3 Lasem teachers. The determination test showed that the variables of competence, work discipline and physical environment were able to affect teacher performance by 89.5% while the remaining 10.5% was explained by other factors.